THE EFFECT OF AMBER ACID ON THE PRODUCTIVITY AND CHEMICAL COMPOSITION OF TOMATOES GROWN IN A CLIMATIC CHAMBER - INNA V. KNYAZEVA; ALEKSEI S. DOROKHOV; OKSANA V. VERSHININA; NINA I. MYACHIKOVA; ANDREI А. GRISHIN; VLADIMIR В. GUDIMO; CECILIA GEORGESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The research was carried out in 2019 - 2020 in the department of closed artificial agroecosystems for plant growing in the Federal State Budgetary Scientific Institution “Federal Scientific Agroengineering Center VIM”, Moscow. The study focused on the seeds of tomatoes (Solanum lycopersicum L.) variety “Lyana”. Amber acid was used as a biostimulating factor at the stage of pre-sowing seed treatment (factor A) and with constant drip irrigation of plants (factor B) throughout the entire growing season – 145 days. The use of аmber acid can increase the crop yield from 2.34 to 3.84 kg/bush when growing tomatoes under controlled conditions in a climatic chamber. Inoculation of seeds with a biostimulant substance promoted an increase in the content of vitamins C (23.23 mg/100 g) and B1 (0.041 mg/100 g) and dry matter (5.06 %) compared to the control. As a result of determining the content of nitrates, it was revealed that the maximum permissible concentration in all samples did not exceed the permissible norm. Thus, the use of amber acid is very promising for growing Lyana tomato plants in artificial agroecosystems.